Effects of mechanical cell disruption on the morphology and properties of spirulina-PLA biocomposites - , Kuotian Liao; Grandgeorge, Paul, Andrew M. Jimenez; Nguyen, Bichlien; Roumeli, Eleftheria (Sustainable Materials and Technologies, 2023)
Biocomposite materials offer a promising strategy to satisfy the increasing demand for sustainable plastics. While the incorporation of biopolymers extracted from plants and microorganisms (e.g., cellulose) as fillers in various polymer matrices has demonstrated encouraging properties, biopolymer extraction often requires wasteful mechanical and chemical treatments, thus limiting the overall environmental benefits. As alternative, an emerging approach makes use of fillers made up of less-refined biological material (biomatter) which retains the original chemical composition and hierarchical structure of the source organism, hence bypassing the energy intensive extraction steps. Here, we introduce a novel set of biocomposite materials obtained by compounding polylactic acid (PLA), one of the most consumed industrially degradable plastics, with spirulina, an abundant and fast-growing microalgal species serving as a filler. Specifically, we study the effect of using spirulina in a raw or physically dissociated form after Sonication. We find that independently of the filler pretreatment, the Young's modulus remains as high as neat PLA, while the elongation to break, strength, and toughness progressively decrease with increasing spirulina content. We show that the use of dissociated spirulina enhances the tensile strength by up to 25% compared to biocomposites made with unprocessed spirulina, as a result of the improved filler dispersion and reduced particle size. Our findings also reveal drastically enhanced moisture-induced plasticization in the biocomposites with dissociated spirulina. We report a remarkable 90% toughness increase with mechanically pretreated spirulina at a concentration of 9.1 wt% when compared to the non-water plasticized biocomposite at the same filler concentration, even rivaling the toughness of neat PLA. Finally, we provide estimates for the reduced global warming potential of the produced biocomposites, as compared to neat PLA. Our study presents a holistic view of the performance of PLA-spirulina biocomposites and demonstrates the effectiveness of physical filler dissociation as a means to improve the strength and toughness of the biocomposites.